Sex differences in the mediators of functional disability in Major Depressive Disorder. (January 2018) - Carmona, Nicole E.; Subramaniapillai, Mehala; Mansur, Rodrigo B.; Cha, Danielle S.; Lee, Yena; Fus, Dominika; McIntyre, Roger S.
Abstract: The aim of this study was to investigate sex differences in discrete domains of psychopathology as mediators of functional disability among individuals with Major Depressive Disorder (MDD). Adults (ages 18–65) with moderate-to-severe MDD ( n = 100) and age-, sex-, and education-matched healthy controls (HC; n = 100) participated in a clinical trial validating the THINC-integrated tool, a newly developed cognitive assessment tool for patients with MDD. Variables assessed as possible mediators included depression symptom severity, anxiety symptoms, sleep disturbance, perceived cognitive deficits, and objective cognitive performance. Functional disability was assessed using the total score on the Sheehan Disability Scale. Separate mediation analyses were conducted for men and women. No significant differences were detected between men and women on the assessed domains of psychopathology or functional disability ( p s > 0.05). However, the mediation analyses demonstrated different patterns with respect to determinants of functional disability in MDD between men and women. Functional disability was mediated by anxiety (95% CI: −3.17, −0.28) and sleep disturbance (95% CI: −0.69, −0.05) among men and by depressive symptom severity (95% CI: −7.82, −0.32) among women. These preliminary results instantiate the need to dimensionalize psychopathology in MDD. Our results at least in part support the hypothesis that, consistent with the sex differences in the prevalence and illness presentation of MDD, determinants of functional outcomes also differ between men and women, underscoring the need to consider sex differences in order to improve functional outcomes in the treatment of MDD.